Onboarding for success: Exploring the effects of socialization tactics on newcomer well-being - Junça-Silva, A.; Faria, C.; Lopes, R. R. (International Journal of Organizational Analysis, 2026)
Purpose This study aimed to examine how the organizational socialization process affects newcomers’ work engagement and well-being. It employed relational cohesion theory and social exchange theory to argue that relational factors, specifically perceived organizational support and on-the-job embeddedness, would act as mechanisms linking the organizational socialization process to key affective outcomes Design/methodology/approach A two-wave study in the chemical industry was conducted. Data was collected during and after the onboarding process with 72 newcomers who joined the organization between January and April of 2023 and completed the organizational onboarding program. Findings The results demonstrated that both perceived organizational support and on-the-job-embeddedness mediated the indirect relationship between socialization tactics used in the onboarding program and work engagement. Further, the findings also demonstrated that work engagement was a mediator in the relationship between perceived organizational support and on-the-job-embeddedness and newcomers’ well-being. Lastly, socialization tactics influenced newcomers’ well-being through a serial effect of perceived organizational support and work engagement and on-the-job embeddedness and work engagement. Originality/value This research highlights the critical role of carefully selected socialization tactics in organizations. By choosing the right approaches, organizations can not only meet their objectives but also gain from the active participation and commitment of their new employees. This, in turn, leads to a significant increase in overall employee well-being.